Highlights of the 2022 American Joint Replacement Registry Annual Report - Vishal Hegde, MD; Jeffrey B. Stambough, MD; Brett R. Levine, MD; Bryan D. Springer, MD (Arthroplasty Today, 2023)
The 2022 American Joint Replacement Registry Annual Report includes data from over 2.8 million hip and knee procedures from over 1,250 institutions that encompass all 50 states and the District of Columbia. This represents a cumulative registered procedural volume growth of 14% compared to the previous year, making the American Joint Replacement Registry the largest arthroplasty registry by volume in the world.